2012
DOI: 10.1186/1476-9255-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Higher IL-6 and IL6:IGF Ratio in Patients with Barth Syndrome

Abstract: BackgroundBarth Syndrome (BTHS) is a serious X-linked genetic disorder associated with mutations in the tafazzin gene (TAZ, also called G4.5). The multi-system disorder is primarily characterized by the following pathologies: cardiac and skeletal myopathies, neutropenia, growth delay, and exercise intolerance. Although growth anomalies have been widely reported in BTHS, there is a paucity of research on the role of inflammation and the potential link to alterations in growth factors levels in BTHS patients.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Saturation of CL leads to defective mitochondrial bioenergetics and explains why BTHS patients have cardiac and skeletal myopathy. It is not known whether changes in CL saturation are also linked to the chronic inflammation and neutropenia in BTHS [810].…”
Section: Introductionmentioning
confidence: 99%
“…Saturation of CL leads to defective mitochondrial bioenergetics and explains why BTHS patients have cardiac and skeletal myopathy. It is not known whether changes in CL saturation are also linked to the chronic inflammation and neutropenia in BTHS [810].…”
Section: Introductionmentioning
confidence: 99%
“…A study of 22 BTHS patients aged between 4 months and 24 years reported subnormal levels of growth hormone (GH) below 14.4 years, but levels higher than controls above this age, most marked at 19–20 years [74]. Insulin-like growth factor-1 (IGF-I) deficiency has been reported; as expected for constitutional growth delay, the patient had normal GH release and no other sign of pituitary dysfunction.…”
Section: Reviewmentioning
confidence: 99%
“…In recent years, overexpression of TAZ has been observed in several tumors, including colon cancer[ 16 ], rectal cancer[ 17 ] and thyroid neoplasms[ 18 ]. Additionally, abnormal TAZ expression combined with higher IL-6 expression was found to promote inflammatory responses, which are commonly considered a predisposition factor for cancer progression[ 19 ]. However, the function of TAZ in cervical carcinogenesis is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%